HUBUNGAN ANTARA KONDISI SOSIAL EKONOMI DENGAN PERSEPSI, SIKAP, DAN PERILAKU MASYARAKAT KABUPATEN KERINCI PADA HUTAN TAMAN NASIONAL KERINCI SEBLAT (TNKS) - Nafril Yuzen; Yusni Ikhwan Siregar; Zulfan Saam (Program Pascasarjana Universitas Riau, 2014)
Kerinci Seblat National Conservation Forest continuously degrade due to illegallogging, uncontrolled land conversion of local people living around the area. Thisunsustainable effort were presumably influenced by social economic factors. This studyaimed at analyzing perception, attitude and behavior of people adjacent to theconservation area. A field survey and interview were performed to 40 respondent oftwo villages namely Kemantan Raya and Pasir Jaya. Data obtained were alayzedfollowing path way analysis. The local people perception on the existence of zkerinciSeblat National Conservation Forest werw apparently positive. They realized that theconservation forest are important for hydrological, biological and economical functionas well as for environment. This study revealed that interrelated of factors (age,educational level, income, job type and family size) of local people did not significantlyrelated to their perception, attitude as well as their behavior. However, age correlated(p›0.05) to perception.